Raman spectral studies of nucleic acids. XVII. Conformational structures of polyinosinic acid. - Chou, C H (1977)
Laser-Raman spectra of poly(rI) show the formation of an ordered complex in aqueous solutions of high ionic strength. This structure exhibits the A-helix geometry, contains stacked bases and is apparently stabilized by specific hydrogen bonding involving hypoxanthine C6=0 groups. Thermal dissociation of the poly(rI) complex (Tm=45 degrees C) yields single-stranded and disordered poly (RI) chains. A disordered structure also occurs for poly (rI) in aqueous solutions of low ionic strength. In oriented films, poly (rI) forms an ordered structure probably the same as that which occurs in solutions of high ionic strength. Raman intensities measured at 815 and 1100 cm-1 in spectra of poly (rI) and poly (rU)-poly (rA)-poly(rU) indicate that the correlation previously established for single- and double-stranded ribopolymer structures is valid also for these multi-stranded structures. X-ray diffraction and model-building studies confirm the A-helix structure.